ASOSIASI PENYAKIT ALERGI ATOPI ANAK DENGAN ATOPI ORANG TUA DAN FAKTOR LINGKUNGAN - Syaiful Ludfi, Achmad; Agustina, Luki; D, Fetarayani; A, Baskoro; S, Gatot; Effendi, Chairul (journal of internal medicine, 2012)
Atopic allergic disease related with genetic factor and environment. Some studies found parents and environment factorhave an important role on emerging of clinical manifestation. This study try to evaluated wheather atopic parents andenvironment can inuanced clinical manifestation of allergic disease in their children. This information is important foreducation and in intervention of treatment for patients with allergic disease. This study is an observasional analytic casecontrol study involved all student range from junior until high school level and their parents at Surabaya region. Datawas taken by quisioner, physical and Skin Prick Test (SPT). Statistical analyses using multivariat logistic regression test.Threehundreed forthy eight student was enrolled where 91 (26.1%) with positive SPT have atopic father 26 (56.9%) andatopic mother 25 (54.3%) on the other hand 249 student with negative SPT have atopic father 22 (43.1%) and atopicmother 21 (45.7%). Logistic regression test found that sequency number of birth and explanation dust mate assosiatedwith occurence of clinical manifestation of atopic allergic disease in children.